Hybrid vascular interventin for multilevel peripheral arterial disease. (14th October 2021) - Puzdriak, P D; Ivanov, M A; Gusinskiy, A V; Shlomin, V V; Bondarenko, P B; Chizhova, K A; Novikova, N Y U; Shvarts, E Y U
Abstract: Objective: To increase the effectiveness of intervention for the lower limb arteries multilevel lesion (MPAD) in patients with type C and D lesions by TASC II classification. Materials and methods: 87 hybrid vascular reconstructions (74 male and 13 female, 59% (n=52) smokers) for MPAD were performed from 2017 to 2020. The average age was 64, 6±8, 1y. CLI was diagnosed in 47% (n=41) by Fontaine- Pokrovsky classification. Following concomitant disease were diagnosed: stage 2–3 of CHF by HYHA classification 33% (n=29), COPD 23% (n=20), arterial hypertension stage 2–3 54% (n=47), CAD 66% (n=58), postinfarction cardiosclerosis 29% (n=26). Registered lesion of iliac-femoral segment type A/B=44 (51%) and C/D=43 (49%); registered lesion of femoro-tibial segment A/B=14 (16%), C/D=73 (84%) by TASC-II classification. Common femoral artery (CFA) bifurcation was most important to perform hybrid intervention. Through CFA with patented method (RU 2621395C) we performed remote endartherectomy from external iliac or superficial femoral arteries, that allowed us to remove a total prolonged occlusion (>15–20 cm), reducing the time and complexity of the endovascular stage. The key note is that we perform CFA plasty with using an autovenous patch with a "trunk" through which we provide endovascular stage of hybrid intervention on natural blood flow, restored after open endartherectomy. This technique allows you to change the direction of introducer in both distal and proximal direction without the need for extra punctures or temporary clamping of the arteries. Results: Technical success rate was 98%. Local aneurysm of EIA was found in one case that restricted to provide the loop endarterectomy. The average duration of hybrid operation was 223, 7±88, 2 min (134, 2±72, 3 min for open and 89, 9±52, 9 for endovascular stages). Average blood loss was 225, 3±130, 7 ml. ICU staying duration was 20, 6±2, 8 hours. 30-days patency was 98, 8%, 12 and 36 months primary patency was 98% and 88, 5% respectively. There were no deaths within 30 days after hybrid operation. The following complications occurred: bleeding n=2 (2, 3%), acute thrombosis n=1 (1, 2%), surgical site infection n=1 (1, 2%) but cured safely. Limb salvage in critical ischemia was in 100% of patients for 20 months. Conclusion: Hybrid surgery of MPAD is highly effective, reduces operation trauma, improves its results and limb salvage. By reducing trauma of surgical intervention reduces admition in ICU, postoperative risks, especially in patients with severe concomitant pathology. Funding Acknowledgement: Type of funding sources: None.